Synthesis, photophysics and two-photon absorption of imidazole-centred tripodal chromophores - Kulhánek, Jiří; Burešová, Zuzana; Klikar, Milan; Sdralias, Lampros; Katsidas, Alexandros; Pytela, Oldřich; Pařík, Patrik; Růžička, Aleš; Fakis, Mihalis; Bureš, Filip (Royal Society of Chemistry, 2024)
Tripodal push-pull chromophores with D-(pi-A)3 arrangement were synthesized using 1-methyl-2,4,5-triphenyl-1H-imidazole as a central electron donor, and their thermal, electrochemical, photophysical and non-linear optical properties were studied and corroborated with quantum-chemical calculations. Their facile synthesis involved Suzuki-Miyaura and Knoevenagel reactions, allowing the installation of various peripheral electron acceptors such as formyl, cyano, ester, trifluoromethyl and more complex moieties such as malonic/acetic acid derivatives, indan-1,3-dione and rhodanine. All phenyl rings appended at the central imidazole core were more or less twisted depending on the peripheral substitution. Although imidazole undergoes reversible one-electron oxidation, peripheral acceptors are reduced irreversibly in a multi-electron process. This behaviour is further seen as a variation of the LUMO, while the HOMO remained almost unaltered across the whole series. TD-DFT calculations revealed centrifugal charge transfer from the central imidazole to all C2, C4 and C5 branches occupied by the LUMO, LUMO+1 and LUMO+2. The HOMO-LUMO gap is tuneable within the range of 3.55-2.31 eV, while the longest-wavelength absorption/emission maxima were found within the broad range of 304-448/393-612 nm. Although the absorption spectra are solvent-independent, the emission depends strongly on the solvent polarity and the electron-withdrawing power of the peripheral acceptors. Extended chromophores with complex electron acceptors were investigated as two-photon absorbers, revealing relatively good cross-section values of up to 521 GM and a figure-of-merit (Phi F x delta 2PA) of around 190 GM. Tripodal imidazole-centred chromophores bearing peripheral acceptors were prepared and investigated. The observed centrifugal ICT results in tuneable (nonlinear) optical properties and two-photon absorption cross-sections of up to 521 GM.
Syntéza, fotofyzikální vlastnosti a dvoufotonová absorpce trojramenných chromofotrů s centrálním jádrem imidazolu
Keywords: push-pull system; chromophore; imidazole; two-photon absorption; non-linear optics; push-pull syst0m; chromofor; imidazol; dvoufotonová absorpce; nelinearní optické vlastrnosti